Scholars’ Corner: Has Jerusalem’s Millo Been Found? (1982)
One of the puzzles British archaeologist Kathleen Kenyon solved during her Jerusalem excavations of 1961-1967 was the meaning of the untranslatable Biblical word Millo. Or did she? On the steep eastern slope of the city of David (or Ophel), the site of the original city of Jerusalem south of the Temple Mount, Kenyon uncovered tier upon tier of architectural terracing buried beneath an avalanche of stone and debris.